Considering the Validity of the SAIL Trial—A Navel Gazers Guide to the SAIL Trial - Kirpalani, Haresh; Keszler, Martin; Foglia, Elizabeth E.; Davis, Peter; Ratcliffe, Sarah (Frontiers in Pediatrics, 2019)
This article explores the validity of the Sustained Aeration Inflation for Infant Lungs (SAIL) randomized controlled clinical trial. The SAIL trial enrolled 460 infants out of a planned 600, but the trial was stopped early for harm. We ask here, whether there were any threats to validity in the trial as conducted. We then explore what design elements of the trial could have been improved upon. Finally we consider what the implications are for future trials in this arena.